ANALISIS USER INTERFACE PADA WEBSITE LPGO MENGGUNAKAN METODE HEURISTICS EVALUATION - Sumakmur Goenawan; Syaiful Rahman; Renny (KHARISMA Tech, 2022)
The purpose of this study was to determine the results of the user interface analysis using heuristics evaluation on the LPGO website so that it can be used as development suggestions. This study uses the Heuristics Evaluation method to generate a severity rating on 10 heuristics evaluation aspects. Based on the research results, it is concluded that the LPGO website has a good user interface because 9 out of 10 aspects have minor problems that are not important and 1 out of 10 aspects have potential problems that can make it difficult for users, namely the help and documentation aspect. Thus, suggestions for improvement can be made on the help and documentation aspect.